2023
DOI: 10.1007/s00423-023-02799-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of serum albumin concentration and neutrophil–lymphocyte ratio score on gastric cancer prognosis

Abstract: INTRODUCTION/AIM -Serum albumin concentration (COA) and neutrophil-lymphocyte ratio (NLR) could reflect immunological and nutritional status. We aim to evaluate the impact of COA-NLR score on the prognosis of gastric cancer (GC). MATERIAL AND METHODS -We perform a retrospective analysis on a database of 637 GC cases, between January 2010 and December 2017. In 396 patients the inclusion criteria for this study were met (non-resectional or palliative surgery were excluded). COA-NLR score was defined as: COA unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…There is a growing body of evidence indicating that the combination of preoperative albumin concentration and the NLR holds predictive value for DFS and OS in patients with Stage I-II GC. 22,23 Additionally, neutrophil count and albumin level 1 month after curative surgery reflect long-term prognosis. 24 Previous study has also shown a correlation between higher NLR and lower serum albumin levels and more advanced clinical staging in GC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a growing body of evidence indicating that the combination of preoperative albumin concentration and the NLR holds predictive value for DFS and OS in patients with Stage I-II GC. 22,23 Additionally, neutrophil count and albumin level 1 month after curative surgery reflect long-term prognosis. 24 Previous study has also shown a correlation between higher NLR and lower serum albumin levels and more advanced clinical staging in GC.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al demonstrated that the NLR and serum albumin could be combined to provide additional risk stratification for ovarian cancer, 21 it has also been reported that the combination of serum albumin and NLR was significantly associated with OS and disease-free survival (DFS) of GC patients submitted to curative surgery. 22,23 However, whether MPS is a predictor of prognosis of advanced GC has not yet been investigated. Therefore, we performed a retrospective study to examine the prognostic significance of the MPS on the survival outcomes of patients with advanced GC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The neutrophil‐lymphocyte ratio (NLR) reflects the host's inflammatory and immune response status. It has been reported in the literature that the NLR has a substantial impact on the prognosis of many malignant tumors, such as NSCLC, gastric cancer, colorectal cancer, and pancreatic cancer 12–15 . Higher NLR values predict poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported in the literature that the NLR has a substantial impact on the prognosis of many malignant tumors, such as NSCLC, gastric cancer, colorectal cancer, and pancreatic cancer. 12 , 13 , 14 , 15 Higher NLR values predict poor prognosis. Correspondingly, coagulation and fibrinolytic system markers, including fibrinogen levels, are associated with tumor progression in different types of malignant tumors.…”
Section: Introductionmentioning
confidence: 99%